1995
DOI: 10.1083/jcb.131.4.951
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of cholera toxin and Escherichia coli heat labile toxin in polarized epithelia: role of COOH-terminal KDEL.

Abstract: Abstract. Vibrio cholerae and Escherichia coli heat labile toxins (CT and LT) elicit a secretory response from intestinal epithelia by binding apical receptors (ganglioside GM1 ) and subsequently activating basolateral effectors (adenylate cyclase). We have recently proposed that signal transduction in polarized cells may require transcytosis of toxin-containing membranes (Lencer, W. I., G. Strohmeier, S. Moe, S. L. Carlson, C. T. Constable, and J. L. Madara. 1995. Proc. Natl. Acad. Sci. USA. 92:10094-10098).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
181
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(190 citation statements)
references
References 69 publications
8
181
0
1
Order By: Relevance
“…In contrast, when these same recombinant toxins were applied to apical membranes, there was little or no delay in the anticipated time course of the secretory response. In all past experiments (11,12,21,25,32), we consistently found that toxin preparations purified from V. cholerae supernatants elicited Cl Ϫ secretion with a shorter lag phase and more rapid rate of onset when applied to basolateral rather than apical surfaces of the same cells (Fig. 1, panel A).…”
Section: Methodsmentioning
confidence: 82%
See 2 more Smart Citations
“…In contrast, when these same recombinant toxins were applied to apical membranes, there was little or no delay in the anticipated time course of the secretory response. In all past experiments (11,12,21,25,32), we consistently found that toxin preparations purified from V. cholerae supernatants elicited Cl Ϫ secretion with a shorter lag phase and more rapid rate of onset when applied to basolateral rather than apical surfaces of the same cells (Fig. 1, panel A).…”
Section: Methodsmentioning
confidence: 82%
“…Cell lysates were precleared again by a 30-min incubation with protein A-Sepharose (Pierce). This procedure solubilizes all cellular proteins and proteins associated with the cell monolayer including the entire fraction of toxin bound to the cell surface or internalized via endocytosis (11,12,25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time course and magnitude of electrogenic Cl Ϫ secretion in T84 cells demonstrated that Ctx (hereafter referred to as CtxAB) was significantly more active than Etx (hereafter referred to as EtxAB); CtxAB exhibited a shorter apparent lag period and generated a higher short circuit current (22). In this paper, we describe the structural basis for this difference in toxicity.…”
mentioning
confidence: 97%
“…The observation that brefeldin A inhibits cholera toxin action (20,21,26), and the presence of a KDEL sequence at that the C terminus of CtxA (RDEL in EtxA) have suggested that the toxin is transported from the TGN to the endoplasmic reticulum (ER). Indeed, mutations in the K(R)DEL sequence of CtxA and EtxA reduce the efficiency of toxin-induced Cl Ϫ secretion in T84 cells (22). It has been speculated that the A-subunit may detach from the B-subunits in the TGN, since only the A-subunit (A1/A2-fragments) has been detected in the ER (23)(24)(25), although transport of the holotoxin from the Golgi to the ER, followed by rapid dissociation and anterograde transport of the B-subunit back to the Golgi, has not been excluded.…”
mentioning
confidence: 99%